2018
DOI: 10.4103/ccd.ccd_746_18
|View full text |Cite
|
Sign up to set email alerts
|

Unveiling the link between prostatitis and periodontitis

Abstract: Background:One of the important tumor markers having critically important applications in every aspect of treating men with prostatic illness is prostate-specific antigen (PSA), formed by prostate acini's epithelial cells. Where prostate is affected by inflammation or malignancy, the PSA levels rise to/and above 4 ng/ml. This study analyzes the interlink between different severity of periodontitis and prostatitis by assessment of PSA antigen levels and periodontal clinical parameters.Materials and Methods:In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 16 publications
1
16
0
1
Order By: Relevance
“…Among the comorbidities investigated in this study, prostatitis was found to have the closest relationship with PC (crude HR 2.07, 95% CI 1.91-2.25, P < 0.001; adjusted HR 1.92, 95% CI 1.77-2.08, P < 0.001). Patients with moderate-to-severe prostatitis and chronic PD were found to have higher prostate-specific antigen levels, which are used to track response to androgen deprivation therapy (ADT) for PC [35]. Famili et al found that men with PC undergoing ADT were more likely to have PD than men not undergoing ADT [36].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the comorbidities investigated in this study, prostatitis was found to have the closest relationship with PC (crude HR 2.07, 95% CI 1.91-2.25, P < 0.001; adjusted HR 1.92, 95% CI 1.77-2.08, P < 0.001). Patients with moderate-to-severe prostatitis and chronic PD were found to have higher prostate-specific antigen levels, which are used to track response to androgen deprivation therapy (ADT) for PC [35]. Famili et al found that men with PC undergoing ADT were more likely to have PD than men not undergoing ADT [36].…”
Section: Discussionmentioning
confidence: 99%
“…Both PD and prostatitis result in cytokine imbalance toward increased pro-inflammatory cytokines, such as interleukine (IL)-6, IL-8, IL-18, TNF-α, and C-reactive protein, and decreased anti-inflammatory cytokines [37]. Additionally, major clinical parameters of PD, especially clinical attachment level, were significantly worse in patients with moderate-to-severe prostatitis [35,37]. Considering the similarity in the etiopathogenesis of prostatitis and PD, it is possible that there is a pathological link between them; however, further studies are necessary to draw a conclusion.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, chronic inflammation has been shown to contribute to or associate with the development of both periodontal and prostatic diseases 7,55,56 . Table 2 summarizes previous epidemiological studies 18,27‐30,57‐69 exploring the associations between periodontal disease and prostatic disease. Thus, it is of great clinical significance to explore the interaction mechanism between these diseases and whether it affects the development and prognosis of the diseases.…”
Section: Epidemiological and Experimental Evidencementioning
confidence: 99%
“…Given the PSA levels in participants with comorbidity of high clinical attachment level (>or = 2.7 mm) and moderate/severe prostatitis higher than those with either condition alone, the association between periodontal disease and PSA level in patients with chronic prostatitis was proposed 4 . Interlink between periodontitis (measured with periodontal clinical parameters) and prostatitis (assessed by PSA antigen levels) was recently proposed based on the observation of patients with chronic prostatitis who also had periodontitis being diagnosed 5 . In that study, an affirmative correlation was noted between PSA and clinical attachment level, probing depths, and plaque index and gingival index scores.…”
Section: Discussionmentioning
confidence: 99%
“…Two previous studies have demonstrated a potential positive association between prostate‐specific antigen (PSA) levels in prostatitis patients and periodontal clinical parameters in periodontitis patients, 4,5 and indicate possible immunological related inflammatory relationship between these two diseases. Because of the presence of similar DNA for periodontal pathogens, particularly for Porphyromonas gingivalis and Treponema denticola , in both prostatic secretion and subgingival dental plaque from the same individual, 6 the authors suggested that oral pathogens might disseminate from their original habitat and reached the prostate and penetrate the intra‐epithelial tissue, causing histologic changes in the organ.…”
Section: Introductionmentioning
confidence: 99%